In-Orbit Calibration of Phase Retardance for Channeled Spectropolarimeter - Youzhi Dong; Xueping Ju; Jing Yuan; Changxiang Yan; Tao Zhang (Sensors, 2023)
The phase retardance of the optical system (PROS) is a crucial factor limiting the accuracy of the Stokes vector reconstruction for the channeled spectropolarimeter. The dependence on reference light with a specific angle of polarization (AOP) and the sensitivity to environmental disturbance brings challenges to the in-orbit calibration of PROS. In this work, we propose an instant calibration scheme with a simple program. A function with a monitoring role is constructed to precisely acquire a reference beam with a specific AOP. Combined with numerical analysis, high-precision calibration without the onboard calibrator is realized. The simulation and experiments prove the effectiveness and anti-interference characteristics of the scheme. Our research under the framework of fieldable channeled spectropolarimeter shows that the reconstruction accuracy of <semantics>S2</semantics> and <semantics>S3</semantics> in the whole wavenumber domain are 7.2 × 10−3 and 3.3 × 10−3, respectively. The highlight of the scheme is to simplify the calibration program and ensure that the PROS high-precision calibration is not disturbed by the orbital environment.